Peran Militer dalam Pemerintahan Fasisme Jerman - Anwar Saragih (Dinamika Politik, 2012)
This study is a study of the role of the military in the government of German fascism. The focus discusses the role of the military in government fascist Germany in the leadership of Adolf Hitler. The findings of this study, there are four important things about the military's role in the government of German fascism: First, civilian control over the military; Second, conflict management in Germany; Third, the concept and strategy of national development; Fourth, lebensraum or power expansion. The method used is descriptive method, which describes an incident in more detail.Keywords: Fascism, militarism, power.